A Closer Outlook at the Curriculum Policy for Disability Students at Islamic Higher Education - Assegaf, Abd Rachman (UIII Press, 2023)
Hidden behind insufficient data, the number of persons with disabilities is growing in surface. Like a pyramid, disability students are high at the primary level but drop off at the secondary, and particularly at the university level. An estimated data (2016) indicates that Indonesian people with disabilities have reached 12,15%. Out of 29 State Islamic Universities (Universitas Islam Negeri or UIN), a very limited number of campuses are inclusive. UIN Yogyakarta is considered the first inclusive campus, while UIN Surabaya is underway. This study tries to look closer at the curriculum policy for disability students at the above-mentioned UINs. The research method applied in this study is a combination of policy analysis and case study. Sources of evidence and information are documentation (digital and printed materials), direct observation and interview with 7 informants. The research findings can be summarized into several points: first, inclusive practices at UINs have gradually developed to meet the global demand for education for all and national policies on disabilities. However, during their learning process, disabled students have met barriers and difficulties in communication, social interaction, and using multimedia and accessible infrastructures. Second, curriculum policies and strategies have already been standardized by the national law of education and adopted by UIN’s authorities into syllabi and subject materials. UIN Yogyakarta has modified Universal Design for Learning (UDL) model, and UIN Surabaya maintains an integrated curriculum to solve the problem of disabilities. Third, both UINs have provided facilities and support systems, hardware and software, but need to be upgraded, and in some cases are ineffective.